The Scottish Labour Party : History, Institutions and Ideas - Hassan, Gerry (Edinburgh University Press, 2004)
Scottish Labour has been the dominant political party in Scotland for over 40 years. Yet this is the first book to consider the contemporary party, analysing it in the context of Scottish politics, Scotland, and the UK, as well as drawing on international comparisons. A range of areas are covered The chronology of events over the life of the party. An analysis of the party, its internal structures and culture, and its role in Scottish society. Labour's role as Scotland's leading party, its institutional role, and its wider relationship with Scottish society. The role of the Labour movement. Key themes include The development of Scottish Labour as Scottish politics has changed with devolution. Its often difficult relationship with devolution. Home rule and the rise of the SNP. The impact of its relationship with the UK Labour party. Includes contributions from Richard Finlay, Michael Keating, Douglas Fraser, Bob McLean and Christopher Harvie. Key Features The first book to look at not only the history of the Scottish Labour Party but also the contemporary party. A mix of contributors ensure a variety of perspectives - from academics, journalists, political commentators and public policy experts. Places Scottish Labour within a national and international context.